EVALUASI KESESUAIAN LAHAN TANAMAN HORTIKULTURA PADA LAHAN KERING DI KECAMATAN EREMERASA KABUPATEN BANTAENG - Saida, Saida; Robbo, Anwar; Haris, Abdul; Numba, Sudirman; Gaozhal, Ahmad (Percetakan Umi Toaha Makassar, 2025)
of Indonesia, from June to July 2023. This study aimed to evaluate the actual and potential suitability classes of horticultural crops and limiting factors. The research method was quantitative descriptive, based on the FAO method modified by the Ministry of Agriculture according to land characteristics. The results showed that tomatoes and chillies in actual land suitability classes 1, 2, 3, 4, 7, 11, 12, 13, 14, 17, and 19 were marginally suitable (S3) and land class 5. Land suitability classes 6, 8, 9, 10, 15, 16, and 18 are unsuitable (N).